A prospective trial to evaluate treatment effects of a β-hydroxy-β-methylbutyrate containing nutrient for leakage at the anastomotic site after esophagectomy - Kanda, Mitsuro (Nagoya J Med Sci, 2020)
Anastomotic leakage after esophagectomy is associated with prolonged hospitalization and increased medical cost. Additionally, it sometimes leads to a fatal condition and impaired postoperative quality of life. During the process of wound healing, β-hydroxy-β-methylbutyrate (HMB) is important for collagen biosynthesis. An open-label prospective intervention trial has been designed to evaluate the treatment effect of an enteral nutrient containing HMB with arginine and glutamine (Abound, Abbott Japan Co., Ltd.) for leakage at the anastomotic site after esophagectomy. Patients in whom leakage at the anastomotic site developed within 14 days after esophagectomy are eligible and Abound (24 g) is administered for 14 days through an enteral feeding tube. The target sample size is 10. The primary endpoint is duration between diagnosis and cure of leakage. Surgical procedure, safety, length of fasting, drainage placement and hospital stay, and nutritional status are determined as secondary endpoints. A historical control consisting of 20 patients who had leakage at the anastomotic site after esophagectomy between 2005 and 2018 at Nagoya University Hospital is compared with enrolled patients.